Influences of Rearing Season, Host Plant, and Silkworm Species on Gut Bacterial Community - Chang Chen; Yujuan Hao; Jiaqi Yang; Jingyu Zhang; Huan Wang; Yanqun Liu (Insects)
The gut bacterial community plays many important roles in the production of nutrients and digestion. Antheraea pernyi and A. yamamai (Lepidoptera: Saturniidae) are two traditional sources of human food, as well as being silk-producing insects. In the present study, the influences of rearing season (spring and autumn), silkworm species (A. pernyi and A. yamamai), and host plant (Quercus wutaishanica and Salix viminalis) on gut microbiota diversity were tested using Illumina MiSeq technology. We found that the bacterial composition and diversity of larvae reared in the autumn are elevated compared to those of larvae from the spring. Silkworm species played an important role in the gut bacterial community. Host plants also affected the diversity of the intestinal flora of the insects: the diversity of the intestinal flora of A. pernyi reared using S. viminalis was higher than those reared using Q. wutaishanica. Our findings provide insights into the gut microbial environment in edible insects.